Molecular Detection and Environment-Specific Diversity of Glycosyl Hydrolase Family 1 β-Glucosidase in Different Habitats - Tiwari, Rameshwar; Kumar, Kanika; Singh, Surender; Nain, Lata; Shukla, Pratyoosh (Frontiers in Microbiology, 2016)
β-glucosidase is a crucial element of the microbial cellulose multienzyme complex since it is responsible for the regulation of the entire cellulose hydrolysis process. Therefore, the aim of the present work was to explore the diversity and distribution of glycosyl hydrolase family 1 β-glucosidase genes in three different environmental niches including, Himalayan soil, cow dung and compost by metagenomic approach. Preliminary evaluation through metabolic profiling using BIOLOG based utilization patterns of carbon, nitrogen, phosphorus and sulphur revealed the environment and substrate specific nature of the indigenous microbial population. Furthermore, clonal library selection, screening and sequence analysis revealed that most of the GH1 β-glucosidase proteins had low identities with the available database. Analysis of the distribution of GH1 β-glucosidase gene fragments and β-glucosidase producing microbial community revealed the environment specific nature. The OTUs obtained from Himalayan soil and compost metagenomic libraries were grouped into 19 different genera comprising 6 groups. The cow dung sample displayed the least diversity of GH1 β-glucosidase sequences, with only 14 genera, distributed among three groups- Bacteroidetes, Firmicutes and Actinobacteria. The metagenomic study coupled with metabolic profiling of GH1 β-glucosidase illustrated the existence of intricate relationship between the geochemical environmental factors and inherent microbial community.